Mesenchymal Stem Cell-Derived Extracellular Vesicles: Emerging Therapies for Neurodegenerative Diseases - Chen P; Wang F; Ling B; Zhu Y; Lin H; Huang J; Wang X (International Journal of Nanomedicine)
Puwen Chen,1,2,* Fangsheng Wang,2,* Baodian Ling,2 Yifan Zhu,1,2 Haihong Lin,1,2 Junyun Huang,1 Xiaoling Wang1 1The First School of Clinical Medicine, Gannan Medical University, Ganzhou, 341000, People’s Republic of China; 2Laboratory Medicine, First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoling Wang, The First School of Clinical Medicine, Gannan Medical University, Ganzhou, People’s Republic of China, Email wangxiaoling1@gmu.cn Junyun Huang, The First School of Clinical Medicine, Gannan Medical University, Ganzhou, People’s Republic of China, Email 13879789666@163.comAbstract: Neurodegenerative diseases are a group of chronic diseases characterized by a gradual loss of neurons that worsens over time and dysfunction. These diseases are extremely harmful, not only affecting the physical health of the patients, but also having a serious impact on their quality of life. They mainly include Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), Amyotrophic lateral sclerosis (ALS), etc. Their pathogenesis is complex, and it is difficult for the existing treatments to effectively slow down the progression of the disease. In recent years, Mesenchymal Stem Cells (MSCs) have received widespread attention for their anti-inflammatory, immunomodulatory and neuroprotective properties. In this context, MSC-derived Extracellular Vesicles (MSC-EVs) have demonstrated unique therapeutic potential as a cell-free therapeutic strategy. MSC-EVs are rich in bioactive substances such as proteins, lipids, mRNAs and miRNAs, which can pass through the blood-brain barrier and be targeted to the diseased area to regulate neuronal survival, synaptic plasticity and neuroinflammatory responses. In addition, compared with stem cell therapy, MSC-EVs have the advantages of low immunogenicity, easy storage and transportation, and avoiding ethical controversies. However, their clinical application still faces challenges: standardized isolation and purification techniques have not been unified, vesicle loading efficiency and targeting need to be further optimized, and long-term safety needs to be systematically evaluated. This review focuses on the role of MSC-EVs in the development of neurological diseases and explores their possible dual roles, both favorable and unfavorable, in the context of neurological diseases. In addition, this review provides a review of current studies on EVs as potential biomarkers for the diagnosis and treatment of neurodegenerative diseases and provides a comprehensive review of the prospects and challenges of MSC-EVs in clinical applications.Keywords: Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, mesenchymal stem cell, extracellular vesicles